1998
DOI: 10.1007/s004310050854
|View full text |Cite
|
Sign up to set email alerts
|

Physical performance in long-term survivors of acute leukaemia in childhood

Abstract: The results of this study provide little evidence for cardiopulmonary impairment in long-term survivors of ALL. Both the cardiac function, as evaluated by ECG and echocardiography, and the physical performance in spiroergometry are normal in a large number of these patients. Anthracycline treatment does not appear to have a negative effect on these parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The study by Matthys et al 13 was excluded because they included in the same group ALL survivors and childhood survivors of several types of cancer other than ALL. The studies from Ostanski et al, 15 Black et al, 16 Kadota et al, 17 Lipshultz et al, 18 Pihkala et al, 19 Calzolari et al 20 Turner-Gomez et al, 21 and Zalewska-Szewczyk et al 22 were excluded from the meta-analysis, because of missing or incomplete description of the methodology (gas analysis) for VO 2peak measurement. The study by Prestor et al 23 A total of 102 childhood survivors of ALL and 99 control subjects from three studies were included in this review (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Matthys et al 13 was excluded because they included in the same group ALL survivors and childhood survivors of several types of cancer other than ALL. The studies from Ostanski et al, 15 Black et al, 16 Kadota et al, 17 Lipshultz et al, 18 Pihkala et al, 19 Calzolari et al 20 Turner-Gomez et al, 21 and Zalewska-Szewczyk et al 22 were excluded from the meta-analysis, because of missing or incomplete description of the methodology (gas analysis) for VO 2peak measurement. The study by Prestor et al 23 A total of 102 childhood survivors of ALL and 99 control subjects from three studies were included in this review (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, female patients show a greater impairment after treatment with anthracyclines, which results in further deterioration of functional capacity and increased body fat compared to males. 13,14,16 For instance, Matthys et al estimated the physical activity of ALL survivors with a questionnaire. Sport leisure time was lower in girl survivors of cancer (the majority, but not all, of which was ALL) than in their corresponding controls.…”
Section: Discussionmentioning
confidence: 99%
“…Given that ALL survivors are at higher risk than the general population for several modifiable health problems, the importance of participating in regular physical activity is even greater for this group. Six cross-sectional studies assessing 220 leukemia survivors in their childhood and adolescent years have reported a mild to moderate reduction in exercise capacity and habitual physical activity levels (21)(22)(23)(24)(25)(26). How these changes extend into adulthood is not known.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, however, we did not see a difference in maximal exercise parameters between pediatric patients and survivors. We previously found a normal cardiopulmonary capacity in 42 of 56 (75%) pediatric and adult long-term survivors undergoing spiroergometric testing 17 years after treatment for ALL [2]. We surmised at that time, in contrast to Odame et al [16], that the decreased fitness may be related to sedentary lifestyle and potential obesity of cancer survivors, rather than the obesity being a result of decreased exercise capacity.…”
Section: Discussionmentioning
confidence: 81%
“…This hypothesis was based on previous reports of a high prevalence of subclinical and clinically evident cardiotoxicity after anthracycline treatment [2,8,11,21,25]. Side effects of anthracyclines can be divided into acute or late toxicity.…”
Section: Discussionmentioning
confidence: 98%